Monoclonal Antibody Therapy in Neuromyelitis Optica Spectrum Disorders: a Meta-analysis of Randomized Control Trials - Kong, Fanxin; Wang, Jianjun; Zheng, Haotao; Cai, Haobin; Hua, Jun; Li, Liling (Frontiers in Pharmacology, 2021)
Background: To update the efficacy and safety data of monoclonal antibodies for the treatment of NMOSD and explore the differences in the effect of treatment between patients seropositive and seronegative for AQP4-IgG. Methods: PubMed, Embase, and Cochrane library published up to July 2020 were searched for randomized controlled trials (RCTs) of monoclonal antibodies treatment (mAb) in patients with NMOSD. The primary outcomes were hazard ratio (HR) for relapse. Secondary outcomes included Expanded Disability Status Scale (EDSS) changes from baseline, adverse events (AEs), and serious adverse events (SAEs). A random-effects model was applied for the effect of heterogeneity among trials. Results: We included 603 patients (monoclonal antibody group, n=382, and control group, n=221) from seven RCTs. There were fewer relapses in the mAb group (HR=0.32, 95%CI: 0.23-0.46, P<0.001), as well as in the AQP4-IgG-seropositive patients (HR=0.18, 95%CI: 0.10-0.32, P<0.001), but not in AQP4-IgG-seronegative NMOSD. Similar results were observed when considering satralizumab only. The mAb had no impact on the changes in EDSS scores from baseline (WMD=-0.21, 95%CI: -0.50-0.09, P=0.176). The mAb did not lead to a higher frequency of AEs (OR=1.18, 95%CI: 0.70-1.98, P=0.529) or SAEs (OR=0.99, 95%CI: 0.63-1.56, P=0.975) compared with the control group. Conclusions: Compared to the control arm, monoclonal antibody therapy showed a significantly better outcome in restraining the HR for relapse among patients with NMOSD but insignificant effects in NMOSD patients with seronegative APQ4-IgG. The safety profile in each arm had no significant difference.